Effects of rice bran phenolics on the structure of rice bran protein under different degrees of rancidity. (15th September 2022) - Zhang, Benpeng; Li, Helin; Li, Fang; Zhou, Qi; Wu, Xiaojuan; Wu, Wei
Abstract: To explore the effects of rice bran endogenous phenolics on rice bran protein under rice bran rancidity-induced oxidation, the structure of non-dephenolized and dephenolized rice bran protein with different degrees of rice bran rancidity (rice bran was stored for 0, 1, 3, 5, and 10 d) were investigated. During rice bran storage, dephenolization increased the carbonyl (from 5.32-24.59 to 6.11–26.52 μmol/g) and free sulfhydryl (from 24.41-32.33 to 32.64–45.04 μmol/g) contents of rice bran protein, and decreased disulfide bonds content (from 24.26-26.61 to 21.78–25.42 μmol/g). Meanwhile, endogenous phenolics improved rice bran protein secondary structural flexibility. Moderate oxidation (rice bran was stored for 0 and 1 d) induced by rice bran rancidity unfolded rice bran protein. The increase of maximum fluorescence emission wavelength red shift and the improvement of surface hydrophobicity induced by endogenous phenolics under moderate oxidation indicated rice bran endogenous phenolics further promoted the unfolding of rice bran protein. Excessive oxidation (rice bran was stored for 3, 5, and 10 d) caused protein aggregation. This work demonstrated that endogenous phenolics significantly affected rice bran protein structure under oxidation, especially the synergistic effect of endogenous phenolics and moderate oxidation on protein unfolding state. Graphical abstract: Image 1 Highlights: The presence of RB endogenous phenolics unfolded RBP structure. Moderate oxidation unfolded RBP, and excessive oxidation promoted RBP aggregation. The RB endogenous phenolics and oxidation synergically affected RBP structure.